The function of food prices in management information systems on public trust - Za, Saida Zainurossalamia; Achmad, Gusti Noorlitaria; Darma, Dio Caisar; Ikbal, Muhammad (Journal of Management, Economics, and Industrial Organization, 2025)
From this paper, we highlight the management information system (MIS) and its role in food prices and public confidence. The case study focuses on nine traditional markets that have existed for a long time until now. To find out the extent of the benefits of MIS developed by the government, we put some questions in a questionnaire distributed to 250 respondents. We focused multiple linear regression analysis on processing data that has collected based on interviews. The results of this important work divided into two categories (direct impact and indirect effect). Regarding food prices, MIS has played a significant role. From other findings, public trust, MIS, and food prices also influence significantly. In the next scenario, by involving food prices as a mediation effect, the contribution will also have a real impact because food prices can have a significant effect on both relationships (MIS and public trust). The price of food is an indicator that plays an important role in this finding. This is because these variables can maintain economic stability in a region through good MIS management in expanding public trust, especially for civilians who want accurate data related to their daily needs. This study’s theoretical contribution integrates the MIS framework, food price dynamics, and public trust to develop a more comprehensive approach to digital transformation governance.